2020
DOI: 10.1017/ice.2020.347
|View full text |Cite
|
Sign up to set email alerts
|

Cluster randomized trial of an antibiotic time-out led by a team-based pharmacist

Abstract: Objective: Antibiotic time-outs (ATOs) have been advocated to improve antibiotic use without dedicated stewardship resources, but their utility is poorly defined. We sought to evaluate the effectiveness of an ATO led by a team-based pharmacist. Design: Cluster randomized controlled trial. Setting: Six medicine teams at an academic medical facility. Patients: Inpatients who received antibiotics and were cared for by a medicine team. Interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…We focused on prescribers who prescribed antimicrobial agents and thus were targeted by pharmacist interventions. Of J o u r n a l P r e -p r o o f the 52 studies, interventions were targeted at or delivered to junior or ward physicians (n=42) [23-31, 34-36, 38-41, 44-49, 51, 53-66, 68-72], specialist physicians (paediatricians, obstetricians, gynaecologists, anaesthetists, or surgeons) (n=12) [22,23,32,33,37,42,43,50,52,64,67,73], and nurses (n=5) [29,43,50,52,67]. The number of patients reviewed by pharmacists was clearly reported in 46 studies [22-33, 35-51, 54, 55, 57-60, 62-68, 70-73].…”
Section: Study Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…We focused on prescribers who prescribed antimicrobial agents and thus were targeted by pharmacist interventions. Of J o u r n a l P r e -p r o o f the 52 studies, interventions were targeted at or delivered to junior or ward physicians (n=42) [23-31, 34-36, 38-41, 44-49, 51, 53-66, 68-72], specialist physicians (paediatricians, obstetricians, gynaecologists, anaesthetists, or surgeons) (n=12) [22,23,32,33,37,42,43,50,52,64,67,73], and nurses (n=5) [29,43,50,52,67]. The number of patients reviewed by pharmacists was clearly reported in 46 studies [22-33, 35-51, 54, 55, 57-60, 62-68, 70-73].…”
Section: Study Findingsmentioning
confidence: 99%
“…A total of 19 studies (2 RCTs and 17 NRS) reported mortality as an outcome. Interventions were not associated with increased mortality in any study [24,38,39,44,48,51,53,55,57,59,60,62,65,66,68,[70][71][72][73]. Three studies (all NRS) reported significant reductions in mortality [55,62,70].…”
Section: (42) Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 16 ]. Another study showed that a team-based, pharmacist-led, time-out strategy using an algorithm potentially promotes oral antimicrobial use [ 36 ]. Exploring more effective time-out strategies for antimicrobial use is needed to bolster the efficacy of time-out.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, teams would be able to make an informed and confident decision to de-escalate, escalate, or appropriately continue antibiotics. A study conducted by Van Schooneveld et al [ 9 ] evaluated an ATO led by a pharmacist which was performed 72 h after antibiotic initiation and after ≤5 days of initiation. The authors did not find a significant difference in antibiotic use, which suggests that timing of the intervention may not be a significant factor.…”
Section: Discussionmentioning
confidence: 99%